Report of seed quality in two Urochloa collections - Florián, David (Bioversity International and the International Center for Tropical Agriculture, 2020)
In order to deliver to donors the hybrid materials that have already been preselected and that are about to be evaluated for commercial release, a count was made of the botanical seed that was available for said delivery. Once the quantities of seed were available, an evaluation process of its quality characteristics was continued, taking into account parameters such as the age of the seed (from the time of harvest to the present), percentage of germination and percentage of viability. Carrying out scarification procedures and the respective necessary germination (Germination in substrate) and viability (Tetrazolium method) tests. Finally, the information obtained was analyzed using descriptive statistics and presented in frequency bar diagrams, in which classifications were made by class, placing the hybrids to be delivered to the donor in each of these classes.